1995
DOI: 10.1002/jnr.490410511
|View full text |Cite
|
Sign up to set email alerts
|

Mitogn induced proliferation of isolated adult mouse schwann cells

Abstract: The proliferation of neonatal Schwann cells (SCs) in response to mitogenic agents has been well analyzed in vitro, but a limited range of mitogens have been defined. We investigated whether three identified neonatal SC mitogens [glial growth factor (GGF), platelet-derived growth factor BB (PDGF-BB), and basic fibroblast growth factor (bFGF)] are required to stimulate mitosis of adult SCs. Adult SCs were isolated from mouse sciatic nerves by mechanical and chemical dissociation, following three experimental ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…Previous studies have shown that GGF2 influences both the motility and proliferation of Schwann cells in vitro (Lemke and Brockes, 1984;Mahanthappa et al, 1996;Zhang et al, 1995;Rutkowski et al, 1995). We have confirmed these effects on acutely denervated Schwann cells, using a concentration of GGF2, which stimulates both.…”
Section: Response To Rhggf2supporting
confidence: 84%
“…Previous studies have shown that GGF2 influences both the motility and proliferation of Schwann cells in vitro (Lemke and Brockes, 1984;Mahanthappa et al, 1996;Zhang et al, 1995;Rutkowski et al, 1995). We have confirmed these effects on acutely denervated Schwann cells, using a concentration of GGF2, which stimulates both.…”
Section: Response To Rhggf2supporting
confidence: 84%
“…forskolin. Schwann cell proliferation is also enhanced by several mitogens, especially heregulin (HRG) proteins, added to the culture medium (Levi et al 1995;Zhang et al 1995). The effects of these factors are potentiated by serum or forskolin .…”
Section: Molecular Markermentioning
confidence: 97%
“…It is also possible that aFGF influences the interaction between injured, sprouting CST fibers and the grafted SCs. Basic FGF may be capable of inducing SC mitogenesis in the presence of other supportive molecules (Peulve et al, 1994;Tzeng et al, 1995;B.T. Zhang et al, 1995).…”
mentioning
confidence: 98%